Optical Manipulation of Nanoparticles’ Flow through Porous Membranes - Mapar, Mokhtar (My University, 2011)
By invention of laser as a high-intensity narrow-band light source and pioneering works of Ashkin, the optical tweezers emerged as a versatile tool for manipulating biological samples and mirco/nano-scale objects. Since then the optical forces have been a mean to trap, levitate and push particles or measure the forces at piconewton scale. To get to this point, many researches have been conducted to study the optical forces and optimize the trapping conditions for different particle sizes and materials. Nevertheless the effect of optical forces on the flow of particles has not been addressed before. The purpose of this thesis is to investigate the effect of light on the flow of nanoparticles. The work includes some nanofabri-cation and silicon work to create a porous membrane using colloidal lithography. PDMS soft lithography has been assisted to form a microfluidic backbone for the silicon device, responsible for delivering colloidal solution to the fabricated membrane and controlling the flow. Then the effect of light has been investigated by studying the flow of nanoparticles through the porous membrane in presence of a converging laser beam in darkfield microscopy setup. The general trend in the experimental results has been postulated by analytical solutions and simulations.
Keywords: Fysik; Physical Sciences